The Role of Ombudsman as A 'Watchdog' in Supporting Public Service Reform - Insan Harapan Harahap; Sergio Kwek (Jurnal Pemerintahan dan Politik, 2025)
This article examines the role of the Ombudsman as a ‘watchdog’ in ensuring accountability and fairness in the public service in Indonesia. Using Watchdog theory, this research explores the role of the Ombudsman as a watchdog institution that safeguards democracy and is responsible for ensuring compliance with public service standards. The Ombudsman has a crucial role in overseeing the government bureaucracy, particularly about maladministration, corruption and abuse of power. The research also illustrates the unique challenges faced by the Ombudsman, due to the limited authority to compel the reported party or agency to comply with the recommendations made by the Ombudsman. The performance report on the Ombudsman's performance in 2023 related to public services shows an increase in the number of reports from the public. However, the increase in the number of reports is an indication of a decline in the quality of public services. The revision of the law to strengthen the Ombudsman's authority is still pending so that reports, conclusions of maladministration, and suggestions for reported parties and their superiors are limited to recommendations.